2015
DOI: 10.1179/1743132815y.0000000079
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin neutralises oxidative stress and nerve growth factor discrepancy in experimental diabetic neuropathy

Abstract: We suggest that neuro-protective effect of NG molecules in sciatic nerve of diabetic rats, through its anti-diabetic as well as antioxidant and anti-inflammatory properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 47 publications
5
39
3
1
Order By: Relevance
“…Secondary risk factors are smoking and prediabetes [1,21,60,63]. Platelet activation [79][80][81][82], oxidative stress [65][66][67][68][69][70][71][72][73][74], low vitamin D [83,84], insulin resistance [58], and genetic factors [100][101][102][103][104][105][106] play another supplementary role, but, for the time being, there are limited options for intervention. A suggestion for targeting insulin resistance originates from the study by Pop-Busui et al, showing that reduced incident DSPN is less frequent in T2D patients receiving insulin-sensitizing oral agents (66%) than in those receiving insulinproviding treatment (66% vs. 72%, respectively, p = 0.02) [155].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary risk factors are smoking and prediabetes [1,21,60,63]. Platelet activation [79][80][81][82], oxidative stress [65][66][67][68][69][70][71][72][73][74], low vitamin D [83,84], insulin resistance [58], and genetic factors [100][101][102][103][104][105][106] play another supplementary role, but, for the time being, there are limited options for intervention. A suggestion for targeting insulin resistance originates from the study by Pop-Busui et al, showing that reduced incident DSPN is less frequent in T2D patients receiving insulin-sensitizing oral agents (66%) than in those receiving insulinproviding treatment (66% vs. 72%, respectively, p = 0.02) [155].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggests that oxidative stress is connected with DSPN [65][66][67][68]. Numerous studies have reported associations between systemic markers of oxidative stress and DSPN in diabetic patients.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…[174][175][176][177][178][179][180] Due to their higher potential activity in many chronic diseases, they are widely used to prepare novel beverages. However, due to the limited oral bioavailability and stability of those compounds, alternative nano-based delivery technologies have been recently studied to assess their efficacy.…”
Section: Nano-naringeninmentioning
confidence: 99%
“…Further, treatment of STZ-induced diabetic rats with 50 and 100 mg/kg/day naringenin (orally for eight weeks) reversed chemical and thermal hyperalgesia and decreased hyperglycemia, as well as restored SOD activity [55]. Al-Rejaje et al demonstrated that naringenin treatment (25 and 50 mg/kg/day) significantly decreased the level of oxidative stress biomarkers and increased NGF in sciatic nerves of STZ-induced diabetic rats [56]. …”
Section: Effect Of Flavonoids On Neuronal Cell Death and Dysfunctionmentioning
confidence: 99%